Effect of sleep deprivation by MMP-WM on rat neurological function and Tau protein in hippocampus: Sleep deprivation via MMP-WM - Cheng, Hong; Gan, Lu; Wang, Yan; Li, Lin; Li, Yongle (Cellular and Molecular Biology, 2023)
An in-depth understanding of the pathogenesis and mechanisms of sleep disorders is important for finding reliable treatments and interventions in the future. This study aims to explore the effect of sleep deprivation by modified multiple platform-water maze (MMP-WM) on rat neurological function and Tau protein in the hippocampus, as well as the intervention effect of remimazolam. First, 40 Sprague Dawley (SD) rats were divided into a control group (no treatment), a Rem group (remimazolam), an MMP-WM group (sleep deprivation model in rats established by MMP-WM), and a combined group (MMP-WM + remimazolam). Five rats were randomly selected from each group for behavior tests at 1 d and 7 d of drug administration or sleep deprivation for Morris water maze and open field test. After that, the rats were executed, the hippocampus was isolated for Nissl staining, and the protein expression of phosphorylated Tau (p-Tau) in the CA1 region of the hippocampus was measured by immunohistochemistry. At 1 d, the status in the MMP-WM group was more similar to that in the control group The MMP-WM group showed sparsely arranged hippocampal CA1 neurons, reduced number of Nissl bodies, prolonged escape latency, decreased number of platform crossings and percentage of activity time in the central region, substantially increased p-Tau expression. In contrast, the combined group showed significant improvement in nerve injury, behavior test results, p-Tau at 7 d compared with the MMP-WM group and the same group at 1 d. In addition, detection of brain-derived neurotrophic factor (BDNF) and neurotransmitter levels in the cerebrospinal fluid also showed improved neurologic function in the combined group. These results confirm tha MMP-WM was effective in the establishment of sleep deprivation rat model that accurately reflects the pathological manifestations of sleep disorders in human, and the use of remimazolam effectively reversed the pathological damage in sleep-deprived rats.